Oral midazolam versus oral triclofos for sedation of children for computed tomography scan - a randomized clinical trial - Gupta, Anushu; Pandey, Maitree; Choudhry, Lalita; Jain, Aruna; Pemde, Harish (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Effective and safe pediatric procedural sedation is still a concern especially in areas outside operation theatres. The aim of the study was to compare the efficacy and safety of oral triclofos and oral midazolam in children undergoing computed tomography. Methods: A prospective randomized double blind study was conducted in 100 children aged one to five years. Group-I (n=50) received oral triclofos 100 mg/kg and Group-II (n=50) oral midazolam 0.75 mg/kg. Both groups were given oral atropine 0.03 mg/kg and supplemented with intravenous midazolam upto 0.1 mg/kg in case of inadequate effect. Onset and duration of sedation, success for completion of procedure and time to recovery were noted. Student’s t test and Z test of proportions were used for statistical analysis. Results Majority of children 36(72%) in Group-I achieved Ramsay Sedation Score >4 as compared to 25(50%) in Group-II. Computed tomography scan could be successfully completed at comparable rate (52% vs 56%). Success rate improved to 96% vs 80% after supplementing intravenous midazolam in Group I & II respectively (p< 0.05). Onset (37.91minutes ± 7.96 vs 26 ± 10), duration of sedation ( 117.91minutes ± 72.41 vs 66.2minutes ± 33) were significantly shorter and recovery (98.19minutes ± 72.58 vs 47.4minutes ± 31.42) in Group I & II respectively was faster in children who received oral midazolam (p< 0.05). Conclusion We conclude that both drugs were equally effective and safe for computed tomography scan in children. However better recovery profile of midazolam makes it more suitable for day care procedures. Journal of Society of Anesthesiologists of Nepal 2015; 2(2): 41-45